2006
DOI: 10.1161/01.hyp.0000237864.65019.a5
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of the TRPM4 Cationic Current in Ventricular Cardiomyocytes From Spontaneously Hypertensive Rats

Abstract: Cardiac hypertrophy is associated with electrophysiological modifications, including modification of action potential shape that can give rise to arrhythmias. We report here a higher detection of a calcium-activated nonselective cation current in cardiomyocytes of spontaneously hypertensive rats (SHRs), a model of hypertension and heart hypertrophy when compared with Wistar-Kyoto (WKY) rat, its normotensive equivalent. Freshly isolated cells from the left ventricles of 3- to 6-month-old WKY rats or SHRs were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 42 publications
10
102
0
Order By: Relevance
“…13 DAG and/or PKC stimulate a calcium-activated nonselective cation channel, such as TRPM4 channel, particularly in the setting of hypertrophy. 8, 26 However, TRPM4 might not participate in the induction of PVC and VT in this model because SK&F96365 inhibits TRPC channels but not TRPM4 channels. 27, 28 In fact, the TRPM4 channel was reported to be expressed more in atrial than in ventricle cardiomyocytes.…”
Section: Roles Of Trpc Channels In Ventricular Arrhythmias In Gαq-tg mentioning
confidence: 88%
“…13 DAG and/or PKC stimulate a calcium-activated nonselective cation channel, such as TRPM4 channel, particularly in the setting of hypertrophy. 8, 26 However, TRPM4 might not participate in the induction of PVC and VT in this model because SK&F96365 inhibits TRPC channels but not TRPM4 channels. 27, 28 In fact, the TRPM4 channel was reported to be expressed more in atrial than in ventricle cardiomyocytes.…”
Section: Roles Of Trpc Channels In Ventricular Arrhythmias In Gαq-tg mentioning
confidence: 88%
“…TRPM4-mediated currents are up-regulated in cardiomyocytes from spontaneous hypertensive rats (40), and gain-of-function mutations in TRPM4 have been associated with familial heart disease (41,42). TRPM4 channel kinetics are finely tuned by diverse cellular factors, including Ca 2ϩ -calmodulin, adenine nucleotides, and phosphoinositide 4,5-bisphosphate (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mast cells, Trpm4 mRNA was also detected in several murine cell types or organs of the cardiovascular system, including heart, endothelial cells, and kidney (20,25), and in rat cerebral artery and smooth muscle cells (26). In the heart, Trpm4 mRNA was amplified from cells of the sinoatrial node (27) and Purkinje fibers (28), and cardiac TRPM4 expression was reported to be upregulated in spontaneously hypertensive rats (29).…”
Section: Introductionmentioning
confidence: 99%